Cutting Tools
By forming a hard carbon film containing amorphous phase and a graphite phase on the substrate of the cutting tool, and forming an interface layer between the substrate and the hard carbon film, the shortened life of the cutting tool when cutting soft metal is solved. The problem is that the tool has long life and efficient cutting.
Patent Information
- Application Number
- CN202080094637.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-04-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-04-24
AI Technical Summary
When using a cutting tool with a hard carbon film to cut materials such as soft metal, it is easy to cause the cutting material to coagulate on the cutting edge part of the tool, resulting in an increase in cutting resistance or a cutting edge defect, thereby shortening the tool life.
Adhesive structure of the substrate and the hard carbon film, where the hard carbon film contains amorphous phase and a graphite phase, with a density between 2.5g/cm3 and 3.5g/cm3, and a crystallinity of no more than 6.5%. The average coordination number of the mass phase is between 2.5 and 4. The thickness of the hard carbon film is preferably between 0.1 μm and 3 μm, the hydrogen content is controlled below 5 atomic percentage, and an interface layer is formed between the substrate and the hard carbon film to improve adhesion.
It effectively suppresses the peeling and defects of the hard carbon film, improves the wear and oxidation resistance of the tool, and extends the life of the tool especially when cutting soft metals.
Smart Images

Figure CN115038539B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to cutting tools. Background Art
[0002] Hard carbon films such as amorphous carbon and diamond-like carbon have excellent wear resistance and lubricity, and are therefore used as coating materials for cutting tools, molds, and machine parts.
[0003] Japanese Patent Application Laid-Open No. 2003-62706 (Patent Document 1) discloses an amorphous carbon-coated tool including a WC-based substrate and an amorphous carbon film coating the substrate.
[0004] International Publication No. 2016 / 190443 (Patent Document 2) discloses a cutting tool including a substrate and a DLC layer located on the surface of the substrate and containing diamond-like carbon.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2003-62706
[0008] Patent Document 2: International Publication No. 2016 / 190443 Summary of the invention
[0009] The cutting tool disclosed herein has:
[0010] A substrate and a hard carbon film disposed on the substrate,
[0011] The hard carbon film includes an amorphous phase and a graphite phase,
[0012] The density of the hard carbon film is 2.5 g / cm 3 Above 3.5g / cm 3 the following,
[0013] The hard carbon film has a crystallinity of 6.5% or less,
[0014] The average coordination number of the amorphous phase is 2.5 or more and 4 or less. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] [ Figure 1 ] Figure 1 This is a cross-sectional view of an example of a cutting tool according to an embodiment of the present disclosure.
[0016] [ Figure 2 ] Figure 2 This is a cross-sectional view of another example of the cutting tool according to one embodiment of the present disclosure.
[0017] [ Figure 3 ] Figure 3 This is an example of an X-ray diffraction pattern of a hard carbon film of a cutting tool according to an embodiment of the present disclosure.
[0018] [ Figure 4 ] Figure 4 For the general Figure 3 The X-ray diffraction pattern shown is a converted pattern obtained by converting the X-axis to represent the wave number and the Y-axis to represent the scattering intensity.
[0019] [ Figure 5 ] Figure 5 For Figure 4 The wave number extracted from the converted pattern shown is The pattern obtained from the area.
[0020] [ Figure 6 ] Figure 6 To use straight line L1 to Figure 5 The spectrum S1 of the extracted pattern is normalized to obtain a standardized spectrum pattern.
[0021] [ Figure 7 ] Figure 7 To show from Figure 6 The spectrum pattern from the amorphous phase is separated from the standardized pattern.
[0022] [ Figure 8 ] Figure 8 To show from Figure 6 The pattern of the peaks originating from the graphite phase separated from the normalized pattern.
[0023] [ Fig. 9 ] Fig. 9 For illustration Figure 6 Figure 2 shows the separation method of Peak A11.
[0024] [ Fig.10 ] Fig.10 For illustration Figure 6 Figure 2 shows the separation method of Peak A12.
[0025] [ Fig.11 ] Fig.11 For illustration Figure 6 Figure 2 shows the separation method of Peak A13.
[0026] [ Fig.12 ] Fig.12 To show the basis Figure 3The graph shows the relationship between the measured interatomic distance and the total correlation function calculated from the X-ray diffraction pattern, and the relationship between the interatomic distance and the total correlation function after fitting using the Reverse Monte Carlo Method.
[0027] [ Fig.13 ] Fig.13 A diagram for illustrating the reverse Monte Carlo method.
[0028] [ Fig.14 ] Fig.14 This is a schematic diagram showing an example of a film forming apparatus used for manufacturing a cutting tool according to an embodiment of the present disclosure.
[0029] [ Fig.15 ] Fig.15 This is a diagram showing an example of a target material used for manufacturing a cutting tool according to an embodiment of the present disclosure. DETAILED DESCRIPTION
[0030] [Problems to be Solved by the Present Disclosure]
[0031] In recent years, the materials being cut have become more diverse, and soft metals such as aluminum alloys, non-ferrous metals such as titanium, magnesium, and copper, organic materials, materials containing hard particles such as graphite, and carbon fiber reinforced plastics (CFRP) have been processed.
[0032] When using a cutting tool having a hard carbon film to cut the above materials, the cut material adheres to the cutting edge of the tool, the cutting resistance increases, or the cutting edge is damaged, so that the tool life tends to be reduced. This is particularly likely to occur when the cut material is a soft metal. Therefore, even when used for cutting soft metals, a cutting tool that can have a long tool life is required.
[0033] The object is therefore to provide a cutting tool which has a long tool life, in particular even when used for cutting soft metals.
[0034] [Effects of the present disclosure]
[0035] According to the present disclosure, it is possible to provide a cutting tool capable of having a long tool life even when used for cutting soft metals in particular.
[0036] [Description of Embodiments of the Present Disclosure]
[0037] First, embodiments of the present disclosure are listed and described.
[0038] (1) The cutting tool disclosed herein comprises:
[0039] A substrate and a hard carbon film disposed on the substrate,
[0040] The hard carbon film includes an amorphous phase and a graphite phase,
[0041] The density of the hard carbon film is 2.5 g / cm 3 Above 3.5g / cm 3 the following,
[0042] The hard carbon film has a crystallinity of 6.5% or less,
[0043] The average coordination number of the amorphous phase is 2.5 or more and 4 or less.
[0044] The cutting tool of the present disclosure can have a long tool life, particularly even when used for cutting soft metals.
[0045] (2) The thickness of the portion of the hard carbon film involved in cutting is preferably 0.1 μm or more and 3 μm or less. This can suppress peeling and chipping of the hard carbon film.
[0046] (3) The hydrogen content of the hard carbon film is preferably 5 atomic % or less. This improves the hardness and oxidation resistance of the hard carbon film.
[0047] (4) It is preferable that the substrate is in contact with the hard carbon film. This improves the adhesion between the substrate and the hard carbon film.
[0048] (5) Preferably, the cutting tool includes an interface layer disposed between the substrate and the hard carbon film.
[0049] The interface layer comprises:
[0050] At least one selected from the group consisting of: a single substance selected from the first group consisting of Group 4 elements, Group 5 elements, Group 6 elements, Group 13 elements, and Group 14 elements excluding carbon of the periodic table, an alloy or a first compound containing at least one element selected from the first group, and a solid solution derived from the first compound; or
[0051] a second compound composed of at least one element selected from the first group and carbon, and one or both of a solid solution derived from the second compound,
[0052] The thickness of the interface layer is greater than 0.5 nm and less than 10 nm.
[0053] Thus, the substrate and the hard carbon film are firmly adhered to each other via the interface layer, and the interface layer plays a role of balancing the hardness difference between the substrate and the hard carbon film, that is, plays a buffering role, so that the impact resistance is also improved.
[0054] (6) The substrate is preferably made of WC-based cemented carbide or cermet. Thus, the cutting tool is suitable for cutting non-ferrous alloys, particularly aluminum alloys, copper alloys, magnesium alloys, and the like.
[0055] (7) The substrate is preferably made of cubic boron nitride. Thus, the cutting tool is suitable for cutting non-ferrous alloys, particularly aluminum alloys, copper alloys, magnesium alloys, and the like.
[0056] [Details of the embodiments of the present disclosure]
[0057] Hereinafter, a specific example of the cutting tool disclosed in the present invention will be described with reference to the accompanying drawings. In the accompanying drawings disclosed in the present invention, the same reference symbols represent the same parts or equivalent parts. In addition, in order to make the drawings clear and simple, the dimensional relationships of length, width, thickness, depth, etc. are appropriately changed, and do not necessarily represent the actual dimensional relationships.
[0058] In this specification, the expression of the form "A to B" refers to the upper and lower limits of a range (i.e., greater than A and less than B). When the unit is not recorded in A but only in B, the unit of A is the same as the unit of B.
[0059] [Embodiment 1: Cutting Tool]
[0060] use Figure 1 and Figure 2 A cutting tool according to one embodiment of the present disclosure (hereinafter also referred to as “this embodiment”) will be described. Figure 1 This is a cross-sectional view of an example of the cutting tool according to the present embodiment. Figure 2 This is a cross-sectional view of another example of the cutting tool according to the present embodiment.
[0061] like Figure 1 As shown, the cutting tool 30 of this embodiment is a cutting tool 30 having a substrate 5 and a hard carbon film 20 disposed on the substrate 5. The hard carbon film 20 includes an amorphous phase 25 and a graphite phase 24. The density of the hard carbon film 20 is 2.5 g / cm 3 Above 3.5g / cm 3 Hereinafter, the crystallinity of the hard carbon film 20 is 6.5% or less, and the average coordination number of the amorphous phase 25 is 2.5 or more and 4 or less.
[0062] The hard carbon film of this embodiment can have a long tool life even when used for cutting soft metals. The reason for this is not clear, but it is presumed to be as follows (i) to (iv).
[0063] (i) In the cutting tool of the present embodiment, the hard carbon film includes an amorphous phase and a graphite phase. When the amorphous phase with a low density includes a graphite phase with a high density, the graphite phase functions as a nanofiller in an organic polymer material. That is, the graphite phase wears appropriately during cutting, reducing the friction caused by the unevenness of the cutting tool surface, thereby suppressing the welding of the cut material.
[0064] (ii) In the cutting tool of this embodiment, the density of the hard carbon film is 2.5 g / cm 3 Above 3.5g / cm 3 When the density of the hard carbon film is within this range, the hardness of the hard carbon film becomes moderate, so that the hard carbon film can have excellent wear resistance.
[0065] (iii) In the cutting tool of the present embodiment, the crystallinity of the hard carbon film is 6.5% or less. When the crystallinity is 6.5% or less, the hardness of the hard carbon film becomes moderate, so that the hard carbon film can have excellent wear resistance.
[0066] (iv) In the cutting tool of the present embodiment, the average coordination number of the amorphous phase is 2.5 or more and 4 or less. When the average coordination number of the amorphous phase is within this range, the hardness of the hard carbon film becomes moderate, so that the hard carbon film can have excellent wear resistance. When the average coordination number of the amorphous phase is 2.5 or less, the hardness decreases, and wear resistance cannot be obtained. In addition, since carbon atoms cannot be more than 4 coordinated, it cannot exceed 4.
[0067] exist Figure 1 In the embodiment, the substrate 5 is in contact with the hard carbon film 20, but the cutting tool of the present embodiment is not limited thereto. Figure 2 As shown, the cutting tool 31 of this embodiment may include an interface layer 21 disposed between the substrate 5 and the hard carbon film 20. In addition, a mixed composition layer (not shown) in which the compositions of these films are mixed, or a gradient composition layer (not shown) in which the composition changes continuously may be provided between the substrate 5 and the interface layer 21. Furthermore, a base layer (not shown) for improving the adhesion between the substrate 5 and the interface layer 21 may be provided.
[0068] The hard carbon film 20 may be arranged to cover the entire surface of the substrate 5 or to cover a portion thereof. When the hard carbon film is arranged to cover a portion of the substrate, it is preferably arranged to cover the surface of at least the portion of the substrate that participates in cutting. In this specification, the portion of the substrate that participates in cutting refers to an area in the substrate that is surrounded by a virtual surface where the distance between the cutting edge ridgeline and the perpendicular line of the tangent line along the cutting edge ridgeline from the cutting edge ridgeline to the substrate side is 2 mm.
[0069] <Base material>
[0070] As the substrate 5, a metal or ceramic substrate can be used. Specifically, there can be cited substrates made of iron, heat-treated steel, WC-based hard alloy, cermet, stainless steel, nickel, copper, aluminum alloy, titanium alloy, aluminum oxide, cubic boron nitride, and silicon carbide. Among them, a substrate composed of WC-based hard alloy, cermet or cubic boron nitride is preferably used.
[0071] <Hard Carbon Film>
[0072] (composition)
[0073] The hard carbon film 20 includes an amorphous phase 25 and a graphite phase 24. Figure 1 In the figure, the graphite phase 24 is shown in a granular form, but the shape of the graphite phase is not particularly limited. The graphite phase may be in a flake form, a layered form of overlapping flakes, or an indefinite shape. The hard carbon film may be composed only of an amorphous phase and a graphite phase.
[0074] In this specification, the determination that the hard carbon film contains an amorphous phase and a graphite phase is performed by X-ray diffraction measurement. The specific confirmation method is described below.
[0075] (A1) The hard carbon film is peeled off from the substrate and filled into a glass capillary (capillary with a diameter of 0.7 mm and a wall thickness of 0.01 mm). X-ray diffraction measurement is performed under the following conditions using high-energy radiation such as Spring-8 to obtain an X-ray diffraction pattern.
[0076] X-ray source: radiation source
[0077] X-ray energy: 35keV
[0078] Entrance slit width: 0.2mm
[0079] Detector: Si element one-dimensional detector
[0080] Diffraction angle 2θ measurement range: 3 to 77°
[0081] Measuring step: 0.005°
[0082] Cumulative time: 15 minutes
[0083] (A2) In the obtained diffraction pattern, five peaks are selected in descending order according to the peak diffraction intensity (CPS) (hereinafter also referred to as "peak intensity"). Among these peaks, if there are three or more peaks whose diffraction angle (2θ) is consistent with the diffraction angle (2θ) of the peak of the graphite crystal, it can be judged that the hard carbon film has a graphite phase. This method is based on the Hanawalt method used for the analysis of X-ray diffraction of conventional crystalline materials. The Hanawalt method is a method of analyzing the diffraction pattern using the peaks with the top three peak intensities.
[0084] It should be noted that the main component of the hard carbon film of the present embodiment is an amorphous phase, so the peak intensity derived from the graphite phase may be relatively weak. In this case, the peak can be confirmed by using a differential spectrum.
[0085] (A3) When a broad peak called a halo pattern is observed in the obtained diffraction pattern, it can be determined that the hard carbon film has an amorphous phase.
[0086] use Figure 3 A specific example of the above-mentioned confirmation method will be described. Figure 3 FIG. 1 is a diagram showing an example of a diffraction pattern of the hard carbon film according to the present embodiment. Figure 3 In the graph, the horizontal axis is the diffraction angle (2θ (degree)), and the vertical axis is the scattering intensity (counts). Figure 3 In the graphite crystal, six peaks with diffraction angles 2θ that are consistent with those of the graphite crystal can be confirmed (in Figure 3 The peaks indicated by the "peaks from the graphite phase" in Figure 3 , the halo pattern represented by “pattern from amorphous phase”).
[0087] (Density of hard carbon film)
[0088] The density of the hard carbon film 20 is 2.5 g / cm 3 Above 3.5g / cm 3 The greater the density of the hard carbon film, the higher the hardness, and the smaller the density, the lower the hardness. When the density of the hard carbon film is within this range, the hardness of the hard carbon film becomes moderate, so that the hard carbon film can have excellent wear resistance.
[0089] The lower limit of the density of the hard carbon film is 2.5 g / cm 3 Above, preferably 2.8 g / cm 3 More preferably, 3.1 g / cm 3 The upper limit of the density of the hard carbon film is 3.5 g / cm 3 Below, preferably 3.4 g / cm 3 The density of the hard carbon film is preferably 3.0 g / cm3 Above 3.5g / cm 3 Below, more preferably 3.2 g / cm 3 Above 3.4g / cm 3 the following.
[0090] The density of the hard carbon film can be measured by an X-ray reflectivity method (measurement device: "SmartLab" (trademark) manufactured by Rigaku Corporation). The measurement conditions of the X-ray reflectivity method are as follows.
[0091] Incident X-ray wavelength: 0.15406nm (CuK line)
[0092] Output: 45kV, 200mA
[0093] Measuring range (angle with sample surface): 0.0~1.0°
[0094] Measuring step: 0.001°
[0095] It should be noted that in the analysis, a range with a good S / N ratio should be used as much as possible.
[0096] (Crystallinity of hard carbon film)
[0097] The crystallinity of the hard carbon film 20 is 6.5% or less. In this specification, the crystallinity of the hard carbon film is an index indicating the ratio of the graphite phase to the amorphous phase in the hard carbon film based on the volume. The smaller the crystallinity, the smaller the ratio of the low-hardness graphite phase, and the higher the hardness of the hard carbon film. When the crystallinity of the hard carbon film is 6.5% or less, the hardness of the hard carbon film becomes moderate, so that the hard carbon film can have excellent wear resistance.
[0098] The upper limit of the crystallinity of the hard carbon film is 6.5% or less, preferably 5.9% or less, and more preferably 5.0% or less. The crystallinity of the hard carbon film is preferably 2% or more and 6.5% or less, and more preferably 3% or more and 5% or less.
[0099] In this specification, the crystallinity of the hard carbon film is measured by the following method. Figure 3 to Figure 11 The details of the measurement method are described below. Figure 3 An X-ray diffraction pattern of an example of the hard carbon film according to the present embodiment is shown, but the shape of the X-ray diffraction pattern is not limited to this.
[0100] (B1) The hard carbon film is subjected to X-ray diffraction measurement in the same manner and under the same conditions as in (A1) above to obtain an X-ray diffraction pattern. Figure 3 shown.
[0101] (B2) The obtained X-ray diffraction pattern ( Figure 3 ) is converted in such a way that the X-axis represents the wave number and the Y-axis represents the scattering intensity. Hereinafter, the converted diffraction pattern is also referred to as the "converted pattern". Figure 4 shown. Figure 4 For the general Figure 3 The X-ray diffraction pattern shown is a diagram converted so that the X-axis represents the wave number and the Y-axis represents the scattering intensity.
[0102] (B3) In the converted pattern, the extracted wave number is The extracted converted pattern is as follows Figure 5 shown. Figure 5 For Figure 4 The wave number extracted from the converted pattern shown is In the graph obtained by measuring the area of , the X-axis represents the wave number and the Y-axis represents the scattering intensity.
[0103] (B4) In the extracted converted pattern (hereinafter also referred to as "extracted pattern"), the wave number on the spectrum S1 is connected by a straight line. The wave number is At the point. Figure 5 In the spectrum S1, the wave number is The point at is represented by S2, and the wave number on the spectrum S1 is The point at is represented by S3, and the straight line connecting S2 and S3 is represented by a dotted line L1.
[0104] (B5) The spectrum is normalized by the above straight line. Figure 6 To illustrate the Figure 5 The X-axis represents the wave number and the Y-axis represents the scattering intensity.
[0105] (B6) The normalized pattern is separated into the spectrum from the amorphous phase and the peak from the graphite phase. Figure 7 To show from Figure 6 The spectrum pattern from the amorphous phase separated from the standardized pattern, where the X-axis represents the wave number and the Y-axis represents the scattering intensity. Figure 8 To show from Figure 6 The pattern of the peak from the graphite phase separated from the normalized pattern, where the X-axis represents the wave number and the Y-axis represents the scattering intensity.
[0106] A specific method for separating the spectrum derived from the amorphous phase and the peak derived from the graphite phase into the above-mentioned standardized pattern will be described later.
[0107] (B7) Find Figure 7 The area SA and Figure 8 The total area SG of the peaks A21, A22, and A23 from the graphite phase is shown. The crystallinity (%) is obtained by calculating the ratio of SG to SA (SG / SA). That is, crystallinity = (SG / SA) × 100. The larger the value of crystallinity, the larger the volume ratio of the graphite phase in the hard carbon film.
[0108] The specific method of separating the spectrum derived from the amorphous phase and the peak derived from the graphite phase into the standardized pattern described in (B6) above is as follows.
[0109] (Method for separating peaks originating from graphite phase)
[0110] exist Figure 6 In the normalized pattern of , the peaks from the graphite phase are assigned. Figure 6 In the above analysis, three peaks A11, A12, and A13 were confirmed. Peak A11 exists at a wave number of The peak A12 is present at a wave number of The peak A13 exists at a wave number of In the range of , it is the peak derived from the (012) plane of the graphite phase.
[0111] (Method for separating Peak A11)
[0112] use Fig. 9 The separation method of Peak A11 will be described. Fig. 9 Indicates for explanation Figure 6 The normalized pattern of the separation method of the peak A11 is shown, with the X-axis representing the wave number and the Y-axis representing the scattering intensity.
[0113] First, at wave number Within the range of , a linear fit is performed on the spectrum S21 to obtain an approximate straight line a1.
[0114] Next, the intersection point a2 of the perpendicular line L2 from the peak top of the peak A11 and the approximate straight line a1 is determined.
[0115] The intersection point a2 and the wave number on the spectrum S21 are The area is approximated by a straight line to obtain an approximate straight line a3.
[0116] The wave number The wave number between the peak A11 and the wave number between the peak A11 and the wave number The approximate straight line a3 is between them, and the range other than this ( Fig. 9 The wave number in is and range) as raw data to produce lines representing the spectrum from the amorphous phase.
[0117] By Figure 6 Subtracting the above-mentioned line representing the spectrum from the amorphous phase from the spectrum shown, we can obtain Figure 8 Peak A21 from the graphite phase is shown.
[0118] (Method for separating Peak A12)
[0119] use Fig.10 The separation method of Peak A12 will be described. Fig.10 Indicates for explanation Figure 6 The normalized pattern of the separation method of the peak A12 is shown, with the X-axis representing the wave number and the Y-axis representing the scattering intensity.
[0120] First, at wave number Within the range of , a linear fit is performed on the spectrum S21 to obtain an approximate straight line b1.
[0121] Next, the intersection point b2 of the perpendicular line L12 from the peak of A12 and the approximate straight line b1 is determined.
[0122] The intersection point b2 and the wave number on the spectrum S21 are The area of is approximated by a straight line to obtain an approximate straight line b3.
[0123] The wave number The wave number between peak A12 and peak A12 is the approximate straight line b1, and the wave number between peak A12 and peak A12 is the approximate straight line b1. The approximate straight line b3 is between them, and the range other than this ( Fig.10 The wave number in is and range) as raw data to produce lines representing the spectrum from the amorphous phase.
[0124] By Figure 6 Subtracting the above-mentioned line representing the spectrum from the amorphous phase from the spectrum shown, we can obtain Figure 8 Peak A22 from the graphite phase is shown.
[0125] (Method for separating Peak A13)
[0126] use Fig.11 The separation method of Peak A13 is described. Fig.11 Indicates for explanation Figure 6 The normalized pattern of the separation method of the peak A13 is shown, with the X-axis representing the wave number and the Y-axis representing the scattering intensity.
[0127] First, at wave number In the range of , a linear fit is performed on the spectrum S1 to obtain an approximate straight line c1.
[0128] Next, the intersection point c2 of the perpendicular line L22 from the peak top of the peak A13 and the approximate straight line c1 is determined.
[0129] The intersection point c2 and the wave number on the spectrum S21 are The area is approximated by a straight line to obtain an approximate straight line c3.
[0130] The wave number The wave number between peak A13 and peak A13 is the approximate straight line c1, and the wave number between peak A13 and peak A13 is the approximate straight line c1. The approximate straight line c3 is between them, and the range other than this ( Fig.11 The wave number in is and range) as raw data to produce lines representing the spectrum from the amorphous phase.
[0131] By Figure 6 Subtracting the above-mentioned line representing the spectrum from the amorphous phase from the spectrum shown, we can obtain Figure 8 Peak A23 from the graphite phase is shown.
[0132] (Method of separating spectrum from amorphous phase)
[0133] By Figure 6 Subtracting the peaks A21, A22, and A23 from the graphite phase separated above from the spectrum shown, we can get the following: Figure 7 Shown is the spectrum from the amorphous phase.
[0134] (Average coordination number of amorphous phase)
[0135] The average coordination number of the amorphous phase 25 is 2.5 to 4. When the average coordination number of the amorphous phase is within this range, the hardness of the hard carbon film becomes appropriate, so that the hard carbon film can have excellent wear resistance.
[0136] The lower limit of the average coordination number of the amorphous phase is 2.5 or more, preferably 3 or more, and more preferably 3.5 or more. The upper limit of the average coordination number of the amorphous phase is 4 or less, and the average coordination number of the amorphous phase is more preferably 3.5 or more and 4 or less.
[0137] In this specification, the average coordination number of the amorphous phase is calculated by the following method. Figure 3 , Fig.12 as well as Fig.13 The calculation method will be described in detail.
[0138] (C1) The hard carbon film is subjected to X-ray diffraction measurement under the same method and conditions as in (A1) above to obtain an X-ray diffraction pattern. An example of an X-ray diffraction pattern of a hard carbon film of a cutting tool according to an embodiment of the present disclosure is as follows: Figure 3 shown.
[0139] (C2) Calculate the total correlation function based on the obtained X-ray diffraction pattern. The total correlation function is calculated by correcting the background and the like of the spectrum obtained by the X-ray diffraction measurement and then using Fourier transform. The total correlation function can be calculated based on the records in the following documents, for example: [Document 1] "Shirayamata", "PDF Analysis Using X-ray Scattering Patterns - Theory and Practice -", Rigaku Journal, Rigaku Co., Ltd., 2019, 50(1), p.1-8; [Document 2] Suzuya Kentaro, "Basics of Analysis of Liquid / Amorphous Structures Using Neutron Diffraction / Total Scattering Methods", RADIOISOTOPES, Japan ISOTOPE Association, 2011, 60, p.63-87.
[0140] (C3) Next, in the full correlation function, the distance between the closest carbon atom pairs (CC) (in Fig.12 In the figure, the range of “interatomic distance” is specified as 0.130 to 0.185 nm to produce a carbon atom structure model that can reproduce the measured peaks in this range. Fig.12 To show the basis Figure 3 The relationship between the measured interatomic distance and the total correlation function calculated from the X-ray diffraction pattern, and the relationship between the interatomic distance and the total correlation function after fitting using the reverse Monte Carlo method. Fig.12 In the graph, the measured peak in the range of interatomic distance of 0.130 to 0.185 nm is represented by P1.
[0141] The reverse Monte Carlo method was used in the preparation of the above carbon atom structure model. Fig.13 is a diagram used to illustrate the reverse Monte Carlo method. Fig.13 As shown, the reverse Monte Carlo method is a simulation method that moves atoms existing in a cubic unit cell having the density of a target substance using random numbers to obtain a structural model that reproduces experimental data such as X-ray diffraction of the target substance. The details of the reverse Monte Carlo method will be described later.
[0142] (C4) Calculate the average coordination number of the amorphous phase based on the obtained carbon atomic structure model.
[0143] (Reverse Monte Carlo method)
[0144] In this specification, the inverse Monte Carlo method is used to fit the measured total correlation function. The procedure of the inverse Monte Carlo method is described in [Document 3] "Shirakawa R., Materia", The Japan Institute of Metals, 1994, Vol. 33, No. 4, p. 400-408.
[0145] In the reverse Monte Carlo method, the total correlation function is calculated based on the obtained model, and the area (S) of the difference between the total correlation function of the model and the measured total correlation function in the distance region (0.140-0.185 nm) is calculated. The fitting is repeated until the value of S becomes 10el 2 / nm or less. Thus, according to the final carbon atom structure model (refer to Fig.13 The average coordination number was calculated.
[0146] (thickness)
[0147] The thickness of the portion of the hard carbon film 20 that participates in cutting (hereinafter, also referred to as "the thickness of the hard carbon film") is preferably 0.1 μm or more and 3 μm or less. In this specification, the portion of the hard carbon film that participates in cutting refers to an area in the hard carbon film that is surrounded by a virtual surface whose distance from the cutting edge ridgeline of the cutting tool and a perpendicular line along the tangent line along the cutting edge ridgeline from the cutting edge ridgeline to the cutting tool side is 2 mm. The thickness of the portion of the hard carbon film that participates in cutting refers to the thickness of the hard carbon film in the area that participates in cutting, starting from the surface of the hard carbon film and along the normal direction of the surface.
[0148] When the thickness of the hard carbon film is 0.1 μm or more, the wear resistance is improved. When the thickness of the hard carbon film is 3 μm or less, the increase of the internal stress accumulated in the hard carbon film can be suppressed, thereby suppressing the peeling and chipping of the hard carbon film.
[0149] The lower limit of the thickness of the hard carbon film is preferably 0.1 μm or more, more preferably 0.5 μm or more, and further preferably 1 μm or more. The upper limit of the thickness of the hard carbon film is preferably 3 μm or less, more preferably 2 μm or less, and further preferably 1.5 μm or less. The thickness of the hard carbon film can be set to 0.1 μm or more and 3 μm or less, 0.5 μm or more and 3 μm or less, 1 μm or more and 3 μm or less, 1 μm or more and 2 μm or less, or 1 μm or more and 1.5 μm or less.
[0150] The thickness of the hard carbon film can be measured by observing the cross section of the hard carbon film using SEM (scanning electron microscope, measuring device: "JSM-6610 series" (trademark) manufactured by JEOL Ltd.). Specifically, the observation magnification of the cross section sample is set to 5000 to 10000 times, and the observation area is set to 100 to 500 μm. 2, measure the thickness at 3 randomly selected locations in one field of view, and take the average value as the "thickness". It should be noted that, as far as the applicant has measured, it can be confirmed that as long as the measurement is performed on the same sample, even if the selected location of the measurement field of view is changed to calculate the measurement result of the thickness multiple times, the measurement result has almost no deviation, and even if the measurement field of view is arbitrarily set, the measurement result is not arbitrary.
[0151] (Hydrogen content)
[0152] The hard carbon film 20 is basically composed of carbon and inevitable impurities, but may contain hydrogen. It is believed that the hydrogen comes from hydrogen and water remaining in the film forming device that enter the hard carbon film during film formation.
[0153] The hydrogen content of the hard carbon film 20 is preferably 5 atomic % or less. As a result, the proportion of sp3 bonds in the hard carbon film increases, thereby increasing the hardness. In addition, the oxidation resistance of the hard carbon film is also improved. The upper limit of the hydrogen content of the hard carbon film is more preferably 4 atomic % or less, and further preferably 2 atomic % or less. The lower limit of the hydrogen content of the hard carbon film is preferably 0 atomic %, but from a manufacturing point of view, it can be 0 atomic %, 1 atomic %, or 2 atomic %. The hydrogen content of the hard carbon film can be set to 0 atomic % or more and 5 atomic %, 0 atomic % or more and 4 atomic %, 0 atomic % or more and 2 atomic %, 1 atomic % or more and 5 atomic %, 1 atomic % or more and 4 atomic %, 1 atomic % or more and 2 atomic %, 2 atomic % or more and 5 atomic %, 2 atomic % or more and 4 atomic %.
[0154] The hydrogen content of the hard carbon film can be measured by using ERDA (Elastic Rebound Particle Detection, measuring device: "HRBS500" manufactured by Kobe Steel). This method is as follows: hydrogen ions that collide with He ions incident at a low angle of incidence are rebounded in the forward direction, and the rebounded hydrogen particles are subjected to energy analysis to measure the amount of hydrogen. It should be noted that, as far as the applicant has measured, it can be confirmed that as long as the measurement is carried out on the same sample, even if the selected position of the measurement field of view is changed to calculate the measurement result of the hydrogen content multiple times, the measurement result has almost no deviation, and even if the measurement field of view is arbitrarily set, the measurement result is not arbitrary.
[0155] (hardness)
[0156] The hardness of the hard carbon film 20 is preferably 35 GPa or more and 75 GPa or less. When the hardness of the hard carbon film is 35 GPa or more, the wear resistance is improved. When the hardness of the hard carbon film is 75 GPa or less, the defect resistance is improved. The lower limit of the hardness of the hard carbon film is preferably 35 GPa or more, more preferably 45 GPa or more, and further preferably 55 GPa or more. The upper limit of the hardness of the hard carbon film is preferably 75 GPa or less, and further preferably 73 GPa or less. The hardness of the hard carbon film is preferably 35 GPa or more and 75 GPa or less, more preferably 45 GPa or more and 73 GPa or less, and further preferably 55 GPa or more and 73 GPa or less.
[0157] The hardness of the hard carbon film can be measured by the nanoindentation method (measurement device: "Nano IndenterXP" (trademark) manufactured by MTS). Specifically, the hardness of three locations on the surface of the hard carbon film is measured, and the average value thereof is used as the "hardness". It should be noted that, as far as the applicant has measured, it can be confirmed that as long as the measurement is performed on the same sample, even if the selected position of the measurement field is changed to calculate the measurement result of the hardness multiple times, the measurement result has almost no deviation, and even if the measurement field is arbitrarily set, the measurement result is not arbitrary.
[0158] <Interface layer>
[0159] like Figure 2 As shown, the cutting tool 31 of the present embodiment may include an interface layer 21 disposed between the substrate 5 and the hard carbon film 20. Thus, the substrate and the hard carbon film are firmly adhered to each other via the interface layer.
[0160] (composition)
[0161] The composition of the interface layer 5 may be as described below in (K1) or (K2).
[0162] (K1) contains at least one selected from the group consisting of the following components: a monomer selected from the first group consisting of Group 4 elements, Group 5 elements, Group 6 elements, Group 13 elements, and Group 14 elements excluding carbon of the periodic table, an alloy containing at least one element selected from the first group, a first compound, and a solid solution derived from the first compound; or
[0163] (K2) contains a second compound composed of at least one element selected from the above-mentioned first group and carbon, and one or both of a solid solution derived from the second compound.
[0164] That is, the interface layer may be in any of the following forms (k1) to (k4).
[0165] (k1) It is composed of at least one selected from the group consisting of a single substance selected from the first group, an alloy containing at least one element selected from the first group, a first compound, and a solid solution derived from the first compound.
[0166] (k2) Contains at least one selected from the group consisting of a single substance selected from the first group, an alloy containing at least one element selected from the first group, a first compound, and a solid solution derived from the first compound.
[0167] (k3) A second compound composed of at least one element selected from the first group and carbon, and one or both of a solid solution derived from the second compound.
[0168] (k4) A second compound composed of at least one element selected from the first group and carbon, and one or both of a solid solution derived from the second compound.
[0169] Here, the Group 4 elements of the periodic table include, for example, titanium (Ti), zirconium (Zr) and hafnium (Hf). The Group 5 elements include, for example, vanadium (V), niobium (Nb) and tantalum (Ta). The Group 6 elements include, for example, chromium (Cr), molybdenum (Mo) and tungsten (W). The Group 13 elements include, for example, boron (B), aluminum (Al), gallium (Ga) and indium (In). The Group 14 elements other than carbon include, for example, silicon (Si), germanium (Ge) and tin (Sn). Hereinafter, the elements contained in the Group 4 elements, the Group 5 elements, the Group 6 elements, the Group 13 elements and the Group 14 elements other than carbon are also referred to as "first elements".
[0170] Examples of alloys containing the first element include Ti-Zr, Ti-Hf, Ti-V, Ti-Nb, Ti-Ta, Ti-Cr, and Ti-Mo. Examples of intermetallic compounds containing the first element include TiCr 2 、Ti 3 Al.
[0171] Examples of the first compound containing the first element include titanium boride (TiB 2 ), zirconium boride (ZrB 2 ), Hafnium Boride (HfB 2 ), vanadium boride (VB 2 ), niobium boride (NbB 2 ), Tantalum boride (TaB 2 ), chromium boride (CrB), molybdenum boride (MoB), tungsten boride (WB), aluminum boride (AlB 2 ).
[0172] The solid solution derived from the first compound mentioned above refers to a state in which two or more of these first compounds are dissolved in each other's crystal structures, and refers to an intrusive solid solution or a substitutional solid solution.
[0173] Examples of the second compound composed of the first element and carbon include titanium carbide (TiC), zirconium carbide (ZrC), hafnium carbide (HfC), vanadium carbide (VC), niobium carbide (NbC), tantalum carbide (TaC), chromium carbide (Cr 3 C 2 ), molybdenum carbide (MoC), tungsten carbide (WC), and silicon carbide (SiC).
[0174] The solid solution derived from the second compound mentioned above refers to a state in which two or more types of the second compounds are dissolved in each other's crystal structure, and refers to an intrusive solid solution or a substitutional solid solution.
[0175] The total content of one monomer selected from the first group, an alloy containing at least one selected from the first group, a first compound, and a solid solution derived from the first compound in the interface layer (hereinafter also referred to as "the content of the first compound, etc.") is preferably from 70 volume % to 100 volume %, more preferably from 80 volume % to 100 volume %, further preferably from 90 volume % to 100 volume %, and most preferably 100 volume %.
[0176] The total content of the second compound in the interface layer and the solid solution derived from the second compound (hereinafter also referred to as "the content of the second compound, etc.") is preferably from 70 volume % to 100 volume %, more preferably from 80 volume % to 100 volume %, further preferably from 90 volume % to 100 volume %, and most preferably 100 volume %.
[0177] The composition of the interface layer, the content of the first compound, etc., and the content of the second compound, etc. can be measured using the transmission electron microscope-energy dispersive X-ray analysis (TEM-EDX: Transmission Electron Microscopy-EnergyDispersive X-ray spectrometry) method. Specifically, the cutting tool is cut using a FIB (focused ion beam device) to expose the interface layer, and the composition of the elements constituting the interface layer, the content of the first compound, etc., and the content of the second compound, etc. are measured while observing the cross section using a TEM. It should be noted that, as far as the applicant has measured, it can be confirmed that as long as the measurement is performed on the same sample, even if the selected position of the measurement field of view is changed to calculate the measurement results multiple times, the measurement results have almost no deviation, and even if the measurement field of view is set arbitrarily, the measurement results are not arbitrary.
[0178] (thickness)
[0179] The thickness of the interface layer 5 is preferably 0.1 nm or more and less than 10 nm. When the thickness of the interface layer is within this range, the effect of improving the adhesion between the substrate and the hard carbon film is increased. The thickness of the interface layer is more preferably 0.5 nm or more and 8 nm or less, and further preferably 1 nm or more and 5 nm or less.
[0180] The thickness of the interface layer can be measured by observing the cross section of the hard carbon film using a SEM (scanning electron microscope). Specifically, the cross section sample is observed at a magnification of 5000 to 10000 times and an observation area of 100 to 500 μm. 2 , measure the thickness at 3 randomly selected locations within one field of view, and take the average value as the "thickness". It should be noted that, as far as the applicant has measured, it can be confirmed that: as long as the measurement is performed on the same sample, even if the selected position of the measurement field of view is changed to calculate the measurement result of the thickness multiple times, the measurement result has almost no deviation, and even if the measurement field of view is arbitrarily set, the measurement result is not arbitrary.
[0181] <Other floors>
[0182] The cutting tool of this embodiment preferably includes a mixed composition layer in which the compositions of these films are mixed, or a gradient composition layer in which the composition changes continuously, between the interface layer and the hard carbon film. This further improves the adhesion between the substrate and the hard carbon film.
[0183] Mixed layers and gradient composition layers cannot necessarily be clearly distinguished. When the manufacturing conditions are switched from the formation of the interface layer to the formation of the hard carbon film, the compositions of the interface layer and the hard carbon film are usually slightly mixed together, thereby forming a mixed composition layer or a gradient composition layer. Although it is difficult to directly confirm these layers, the existence of these layers can be fully inferred from the results of XPS: (X-ray Photo-electronic Spectroscopy) or AES: (Auger Electron Spectroscopy).
[0184] <Application of cutting tools>
[0185] The cutting tool of this embodiment has excellent wear resistance and welding resistance, and is therefore particularly suitable for processing aluminum and its alloys. In addition, it is also suitable for processing non-ferrous materials such as titanium, magnesium, and copper. In addition, it is also suitable for cutting materials containing hard particles such as graphite or organic materials, printed circuit board processing, and co-cutting of iron-based materials and aluminum. In addition, the hard carbon film of the cutting tool of this embodiment has a very high hardness, so it can be used not only for non-ferrous materials, but also for processing steel such as stainless steel or castings.
[0186] <Types of cutting tools>
[0187] The cutting tool of this embodiment can be used as, for example, a drill, an end mill, an indexable cutting insert for end milling, an indexable cutting insert for milling, an indexable cutting insert for turning, a metal saw, a gear cutting tool, a reamer, and a tap.
[0188] [Embodiment 2: Method for manufacturing cutting tool]
[0189] The cutting tool of the first embodiment can be used, for example, Fig.14 The film forming apparatus 1 shown is used to form a hard carbon film on a substrate. Next, an example of a method for manufacturing a cutting tool will be described.
[0190] (Preparation of substrate)
[0191] A substrate 5 is prepared. As the type of the substrate, the materials described in Embodiment 1 can be used. For example, the substrate is preferably made of WC-based cemented carbide, cermet, or cubic boron nitride.
[0192] The substrate 5 is mounted on the substrate holder 4 in the film forming apparatus 1. The substrate holder 4 rotates between the targets 2 and 3 with the center point of the targets 2 and 3 as the center.
[0193] The substrate 5 is heated to 200° C. using the substrate heater 6, and the vacuum degree in the film forming apparatus 1 is set to 5×10 - 4 Next, the set temperature of the substrate heater 6 was lowered to a substrate temperature of 100° C., and then argon gas was introduced and maintained at 2×10 -1 Pa atmosphere, and at the same time, a voltage of -1000 V is applied to the substrate holder 4 by the film forming bias power supply 9 to perform argon plasma cleaning on the substrate surface. Then, the argon gas is exhausted. In the film forming apparatus 1, the gas is supplied through the gas supply port 10, and the gas is exhausted through the exhaust port 11.
[0194] Next, a target material 2 composed of a Group 4 element, a Group 5 element, or a Group 6 element of the periodic table is placed in the film forming apparatus 1 .
[0195] The target material 2 is evaporated and ionized, and a voltage of -600 V is applied to the substrate holder 4 by the bias power supply 9 to perform metal ion bombardment treatment. As a result, the surface of the substrate is etched, and the adhesion with the interface layer or hard carbon film to be formed later is improved.
[0196] It should be noted that the formation of the interface layer and the formation of the hard carbon film described below may be performed without subjecting the substrate to the metal ion bombardment treatment.
[0197] (Formation of interface layer)
[0198] Next, a target material 2 composed of one element selected from the group consisting of Group 4 elements, Group 5 elements, Group 6 elements, Group 13 elements, and Group 14 elements other than carbon in the periodic table is arranged in the film forming apparatus 1. With or without the introduction of hydrocarbon gas, the target material 2 is evaporated and ionized by vacuum arc discharge, and a voltage of -100V to -800V is applied to the substrate holder 4 by the bias power supply 9 to form an interface layer on the substrate. Then, the hydrocarbon gas is exhausted.
[0199] It should be noted that the hard carbon film described later may be formed without forming an interface layer on the substrate.
[0200] (Formation of Hard Carbon Film)
[0201] Next, a target material 3 composed of glassy carbon is arranged in the film forming apparatus 1. Argon gas is introduced at a flow rate of 10cc / min, and the target material 3 is evaporated and ionized by vacuum arc discharge (cathode current 120A), and a voltage of -40V to -200V is applied to the substrate holder 4 by a bias power supply 9 to form a hard carbon film on the interface layer, thereby obtaining a cutting tool.
[0202] Commercially available glassy carbon can be used. Glassy carbon is a high-purity carbon material, and compared with the sintered body of carbon (sintered graphite, etc.) used in conventional cathodes, it is not contaminated by metal elements. In particular, the glassy carbon manufactured by Hitachi Chemical Co., Ltd. does not contain aluminum (Al), and is therefore particularly suitable for cutting aluminum alloys. In addition, when glassy carbon is used, the generation of macroscopic particles in the hard carbon film can be suppressed, thereby obtaining a smooth hard carbon film and improving cutting performance.
[0203] The target material is usually cylindrical, disc-shaped or rectangular. However, the inventors have made a new discovery after intensive research: from the perspective of improving the film quality of the hard carbon film, Fig.15 The triangular prism shape shown is preferred. Sometimes a high current needs to flow through the target, but by using a V-shaped electrode and making the side of the target close to the electrode, the target can be stably powered. Furthermore, since the target is close to the electrode, the cooling effect can also be improved. By effectively cooling the target, the resistance is reduced, so that the arc point is easy to move. As a result, the generation of defects in the hard carbon film can be suppressed, thereby improving the film quality of the hard carbon film.
[0204] From the viewpoint of improving the purity of the hard carbon film, it is preferable to form the film in a vacuum without introducing Ar gas. However, the present inventors have made a new discovery after intensive research that arc discharge is more stable when Ar gas is passed at a flow rate of 10 cc / min than in a vacuum, thereby improving the film quality.
[0205] Example
[0206] This embodiment will be described in more detail with reference to examples, but this embodiment is not limited to these examples.
[0207] 《Example 1》
[0208] [Manufacturing of cutting tools]
[0209] <<Sample 1 to Sample 3, Sample 7>>
[0210] In Samples 1 to 3 and 7, glassy carbon was used as a raw material, and a cathode arc ion plating method (referred to as "arc method" in Table 1) was used to sequentially form an interface layer and a hard carbon film on a substrate to produce a cutting tool.
[0211] <Sample 1>
[0212] (Preparation of substrate)
[0213] Prepared A drill made of WC (grain size: 1 μm) based cemented carbide was used as a substrate. The substrate contained 8 mass % of Co as a bonding material.
[0214] Install the substrate Fig.14 In the film forming apparatus 1 shown in the figure, the substrate is heated to 200° C. using the substrate heater 6, and the vacuum degree in the film forming apparatus 1 is set to 5×10 -4 Then, the set temperature of the substrate heater 6 was lowered to 100° C., and then argon gas was introduced and maintained at 2×10 -1 Pa atmosphere, and a voltage of -1000 V was applied to the substrate holder 4 by the film forming bias power supply 9 to perform argon plasma cleaning on the substrate surface. Then, the argon gas was exhausted.
[0215] (Formation of interface layer)
[0216] Next, hydrocarbon gas was introduced into the film forming device 1 at a flow rate of 10 cc / min, and a triangular prism-shaped target material composed of chromium (Cr) was evaporated and ionized by vacuum arc discharge (cathode current 80 A), and a voltage of -800 V was applied to the substrate holder 4 by the bias power supply 9 to form an interface layer composed of chromium carbide (CrC) with a thickness of 5 nm on the substrate. Then, the hydrocarbon gas was exhausted.
[0217] (Formation of Hard Carbon Film)
[0218] Next, argon gas is introduced into the film forming device 1 at a flow rate of 10cc / min, and at the same time, a triangular prism-shaped target material composed of glassy carbon ("glassy carbon" manufactured by Hitachi Chemical Co., Ltd.) is evaporated and ionized by vacuum arc discharge (cathode current 120A), and a voltage of -200V is applied to the substrate holder 4 by a bias power supply 9 to form a hard carbon film with a thickness of 0.6μm on the interface layer, thereby obtaining a cutting tool.
[0219] <Sample 2>
[0220] (Preparation of substrate)
[0221] The substrate was prepared in the same manner as Sample 1.
[0222] (Formation of interface layer)
[0223] Next, a target material composed of chromium (Cr) is evaporated and ionized by vacuum arc discharge (cathode current 80A) without introducing gas into the film forming apparatus 1, and a voltage of -800 V is applied to the substrate holder 4 by the bias power supply 9 to form an interface layer composed of chromium carbide (CrC) with a thickness of 5 nm on the substrate. Then, the hydrocarbon gas is exhausted.
[0224] (Formation of Hard Carbon Film)
[0225] Next, argon gas is introduced into the film forming device 1 at a flow rate of 10cc / min, and at the same time, a triangular prism-shaped target material composed of glassy carbon ("glassy carbon" manufactured by Hitachi Chemical Co., Ltd.) is evaporated and ionized by vacuum arc discharge (cathode current 120A), and a voltage of -150V is applied to the substrate holder 4 by a bias power supply 9 to form a hard carbon film with a thickness of 0.4μm on the interface layer, thereby obtaining a cutting tool.
[0226] <Sample 3>
[0227] (Preparation of substrate)
[0228] The substrate was prepared in the same manner as Sample 1.
[0229] (Formation of interface layer)
[0230] Next, hydrocarbon gas was introduced into the film forming device 1 at a flow rate of 10 cc / min, and a triangular prism-shaped target material composed of titanium (Ti) was evaporated and ionized by vacuum arc discharge (cathode current 80 A), and a voltage of -100 V was applied to the substrate holder 4 by the bias power supply 9 to form an interface layer composed of titanium carbide (TiC) with a thickness of 5 nm on the substrate. Then, the hydrocarbon gas was exhausted.
[0231] (Formation of Hard Carbon Film)
[0232] Next, argon gas is introduced into the film forming device 1 at a flow rate of 10cc / min, and at the same time, a triangular prism-shaped target material composed of glassy carbon ("glassy carbon" manufactured by Hitachi Chemical Co., Ltd.) is evaporated and ionized by vacuum arc discharge (cathode current 120A), and a voltage of -100V is applied to the substrate holder 4 by a bias power supply 9 to form a hard carbon film with a thickness of 0.6μm on the interface layer, thereby obtaining a cutting tool.
[0233] <Sample 7>
[0234] (Preparation of substrate)
[0235] The substrate was prepared in the same manner as Sample 1.
[0236] (Formation of interface layer)
[0237] Next, without introducing gas into the film forming device 1, a target material composed of titanium (Ti) is evaporated and ionized by vacuum arc discharge (cathode current 80A), and a voltage of -800 V is applied to the substrate holder 4 by the bias power supply 9 to form an interface layer composed of titanium (Ti) with a thickness of 5 nm on the substrate. Then, the hydrocarbon gas is exhausted.
[0238] (Formation of Hard Carbon Film)
[0239] Next, argon gas is introduced into the film forming device 1 at a flow rate of 10cc / min, and at the same time, a triangular prism-shaped target material composed of glassy carbon ("glassy carbon" manufactured by Hitachi Chemical Co., Ltd.) is evaporated and ionized by vacuum arc discharge (cathode current 120A), and a voltage of -40V is applied to the substrate holder 4 by a bias power supply 9 to form a hard carbon film with a thickness of 0.6μm on the interface layer, thereby obtaining a cutting tool.
[0240] <<Sample 4 to Sample 6, Sample 8>>
[0241] In Samples 4 to 6 and 8, glassy carbon was used as a raw material, and a hard carbon film was formed on a substrate by a cathode arc ion plating method to produce a cutting tool.
[0242] <Samples 4 to 6, Sample 8>
[0243] (Preparation of substrate)
[0244] The substrate was prepared in the same manner as Sample 1.
[0245] (Formation of Hard Carbon Film)
[0246] Next, argon gas was introduced into the film forming apparatus 1 at a flow rate of 10 cc / min, and a triangular prism-shaped target material composed of glassy carbon ("glassy carbon" manufactured by Hitachi Chemical Co., Ltd.) was evaporated and ionized by vacuum arc discharge (cathode current 120A), and the voltage shown in the "Bias voltage (V)" column of Table 1 was applied to the substrate holder 4 by the bias power supply 9 to form a hard carbon film on the substrate, thereby obtaining a cutting tool. The thickness of the hard carbon film of each sample is shown in the "Thickness (μm)" column of the "Hard carbon film" in Table 1.
[0247] <Sample 9>
[0248] In Sample 9, sintered graphite was used as a raw material, and a hard carbon film was formed on a substrate by cathode arc ion plating to produce a cutting tool.
[0249] (Preparation of substrate)
[0250] The substrate was prepared in the same manner as Sample 1.
[0251] (Formation of Hard Carbon Film)
[0252] Next, argon gas was introduced into the film forming device 1 at a flow rate of 10 cc / min, and a triangular prism-shaped target material composed of sintered graphite ("IG-510" manufactured by Toyo Tanso Co., Ltd.) was evaporated and ionized by vacuum arc discharge (cathode current 120A), and a voltage of -100 V was applied to the substrate holder 4 by the bias power supply 9 to form a hard carbon film with a thickness of 0.6 μm on the substrate, thereby obtaining a cutting tool. It should be noted that droplets were confirmed on the surface of the sample.
[0253] <Sample 10>
[0254] As Sample 10, a sample was prepared in which a cutting tool was produced by the same production method as Sample 9, and the surface of the hard carbon film was polished with elastic abrasive grains impregnated with diamond abrasive grains to remove droplets on the surface.
[0255] <<Sample 11>>
[0256] In Sample 11, a hard carbon film having a thickness of 0.6 μm was formed on the same substrate as that of Sample 1 by a plasma CVD method using methane gas as a raw material, thereby producing a cutting tool.
[0257] [evaluate]
[0258] (X-ray diffraction measurement)
[0259] The hard carbon film of each sample was subjected to X-ray diffraction measurement. The obtained X-ray diffraction spectrum was subjected to peak separation by the method described in the first embodiment, thereby separating the peak derived from the graphite phase and the spectrum derived from the amorphous phase.
[0260] In samples 1 to 10, a peak derived from the graphite phase and a spectrum derived from the amorphous phase were confirmed. This indicates that the hard carbon films of samples 1 to 10 include the graphite phase and the amorphous phase.
[0261] In Sample 11, only the spectrum derived from the amorphous phase was confirmed, and no peak derived from the graphite phase was confirmed. This means that the hard carbon film of Sample 11 does not contain a graphite phase.
[0262] (Determination of Hydrogen Content)
[0263] The hydrogen content of the hard carbon film of each sample was measured. The method for measuring the hydrogen content is described in Embodiment 1, so the description thereof will not be repeated. The results are shown in the "Hydrogen content (atomic %)" column of Table 1.
[0264] (Determination of hardness)
[0265] The hardness of the hard carbon film of each sample was measured. The method for measuring the hardness is described in Embodiment 1, so the description thereof will not be repeated. The results are shown in the column "Hardness (GPa)" of Table 1.
[0266] (Determination of density)
[0267] The density of the hard carbon film of each sample was measured. The method for measuring the density is described in Embodiment 1, so the description thereof will not be repeated. The results are shown in Table 1, “Density (g / cm 3 )” column.
[0268] (Determination of crystallinity)
[0269] The crystallinity of the hard carbon film of each sample was measured. The method for measuring the crystallinity is described in Embodiment 1, so the description thereof will not be repeated. The results are shown in the "Crystallinity (%)" column of Table 1.
[0270] (Determination of average coordination number)
[0271] The average coordination number of the amorphous phase of the hard carbon film of each sample was measured. The method for measuring the average coordination number is described in Embodiment 1, so the description thereof will not be repeated. The results are shown in the "Coordination Number (Coordination)" column of Table 1.
[0272] (Cutting test)
[0273] Using the cutting tool of each sample, drilling was performed under the following cutting conditions.
[0274] Cutting material: ADC12 (Al-Si-Cu alloy)
[0275] Cutting speed: 200m / min
[0276] Feed speed: 0.4mm / rev
[0277] Hole depth: 23mm stop
[0278] Coolant: Internal oil supply 1.9MPa
[0279] The number of holes processed from the time when the tip of the drill bit was worn and aluminum alloy was condensed until a defect (500 μm or more) was formed was measured. The more holes processed, the better the wear resistance and the longer the tool life. The results are shown in the "Number of holes processed" column of "Cutting test" in Table 1.
[0280]
[0281] <Investigation>
[0282] The cutting tools of samples 1 to 7 correspond to the examples, and the cutting tools of samples 8 to 11 correspond to the comparative examples.
[0283] It was confirmed that, compared with Samples 8 to 11 (Comparative Examples), Samples 1 to 7 (Examples) had a greater number of machined holes, were superior in wear resistance, and had a longer tool life.
[0284] It is believed that the density of the hard carbon film of Sample 8 is less than 2.5 g / cm 3 And the crystallinity exceeds 6.5%, so the hardness is low, the wear resistance is reduced, and the tool life is short.
[0285] It is considered that since the crystallinity of the hard carbon film of Samples 9 and 10 exceeded 6.5%, the hardness was low, the wear resistance was reduced, and the tool life was short.
[0286] It is considered that the hard carbon film of Sample 11 does not contain a graphite phase, has low hardness, reduced wear resistance, and short tool life.
[0287] 《Example 2》
[0288] <<Sample 2-1>>
[0289] (Preparation of substrate)
[0290] As a substrate, a cermet insert having an insert number of DCGT11T308 was prepared. By the same method as that of Sample 1, the surface of the substrate was cleaned with argon plasma.
[0291] (Formation of Hard Carbon Film)
[0292] Next, a hard carbon film having a thickness of 0.6 μm was formed on the substrate under the same conditions as those of Sample 1, thereby obtaining a cutting tool.
[0293] <<Sample 2-2>>
[0294] Sample 2-2 is the same insert as the insert prepared in Sample 2-1. Sample 2-2 does not have a hard carbon film.
[0295] [evaluate]
[0296] (X-ray diffraction measurement)
[0297] The hard carbon film of Sample 2-1 was subjected to X-ray diffraction measurement, and the obtained X-ray diffraction spectrum was subjected to peak separation by the method described in Embodiment 1, thereby separating the peak derived from the graphite phase and the spectrum derived from the amorphous phase.
[0298] In sample 2-1, a peak derived from the graphite phase and a spectrum derived from the amorphous phase were confirmed, which means that the hard carbon film of sample 2-1 contains the graphite phase and the amorphous phase.
[0299] (Determination of hydrogen content, determination of hardness, determination of density, determination of crystallinity, determination of average coordination number)
[0300] The hard carbon film of sample 2-1 was subjected to measurement of hydrogen content, hardness, density, crystallinity, and average coordination number of the amorphous phase. Each measurement method is described in Implementation 1, so the description thereof will not be repeated. The results are shown in Table 2, "Hydrogen content (atomic %)", "Hardness (GPa)", "Density (g / cm 3 )", "Crystallinity (%)", and "Coordination number (coordination)" columns.
[0301] (Cutting test)
[0302] Using the cutting tool of each sample, round bar turning was performed under the following cutting conditions.
[0303] Cutting material: ADC12 (Al-Si-Cu alloy) round bar
[0304] Cutting speed: 300m / min
[0305] Feed speed: 0.2mm / rev
[0306] Cutting amount: 1.0mm
[0307] Cutting oil: 0.4MPa
[0308] The cutting length (km) until the tool was damaged (500 μm or more) due to cutting edge adhesion was measured. The longer the cutting length, the better the defect resistance and the longer the tool life. The results are shown in the "Cutting Length" column of "Cutting Test" in Table 2.
[0309] [Table 2]
[0310]
[0311] <Investigation>
[0312] The cutting tool of Sample 2-1 corresponds to the Example. The cutting tool of Sample 2-2 corresponds to the Comparative Example. It was confirmed that Sample 2-1 (Example) had a longer cutting length, excellent defect resistance, and a longer tool life than Sample 2-2 (Comparative Example).
[0313] 《Example 3》
[0314] <<Sample 3-1>>
[0315] (Preparation of substrate)
[0316] As a substrate, a cubic boron nitride blade having a blade number of VBGW160408 was prepared. In the same manner as in Sample 1, the surface of the substrate was cleaned with argon plasma.
[0317] (Formation of Hard Carbon Film)
[0318] Next, a hard carbon film having a thickness of 0.6 μm was formed on the substrate under the same conditions as those of Sample 1, thereby obtaining a cutting tool.
[0319] <<Sample 3-2>>
[0320] Sample 3-2 is the same insert as the insert prepared in Sample 3-1. Sample 3-2 does not have a hard carbon film.
[0321] [evaluate]
[0322] (X-ray diffraction measurement)
[0323] The hard carbon film of Sample 3-1 was subjected to X-ray diffraction measurement, and the obtained X-ray diffraction spectrum was subjected to peak separation by the method described in Embodiment 1, thereby separating the peak derived from the graphite phase and the spectrum derived from the amorphous phase.
[0324] In sample 3-1, a peak derived from the graphite phase and a spectrum derived from the amorphous phase were confirmed, which means that the hard carbon film of sample 3-1 contains the graphite phase and the amorphous phase.
[0325] (Determination of hydrogen content, determination of hardness, determination of density, determination of crystallinity, determination of average coordination number)
[0326] The hard carbon film of sample 3-1 was subjected to measurement of hydrogen content, hardness, density, crystallinity, and average coordination number of the amorphous phase. Each measurement method is described in Implementation 1, so the description thereof will not be repeated. The results are shown in Table 3, "Hydrogen content (atomic %)", "Hardness (GPa)", "Density (g / cm 3 )", "Crystallinity (%)", and "Coordination number (coordination)" columns.
[0327] (Cutting test)
[0328] Using the cutting tool of each sample, round bar turning was performed under the following cutting conditions.
[0329] Cutting material: ADC12 (Al-Si-Cu alloy) round bar
[0330] Cutting speed: 500m / min
[0331] Feed speed: 0.15mm / rev
[0332] Cutting amount: 0.5mm
[0333] Cutting oil: external oil supply 0.4MPa
[0334] The cutting length (km) until the tool was damaged (500 μm or more) due to cutting edge adhesion was measured. The longer the cutting length, the better the damage resistance and the longer the tool life. The results are shown in the "Cutting Length" column of "Cutting Test" in Table 3.
[0335] [Table 3]
[0336]
[0337] <Investigation>
[0338] The cutting tool of Sample 3-1 corresponds to the Example. The cutting tool of Sample 3-2 corresponds to the Comparative Example. It was confirmed that Sample 3-1 (Example) has a longer cutting length, excellent defect resistance, and a longer tool life than Sample 3-2 (Comparative Example).
[0339] As mentioned above, although the embodiment and the example of the present disclosure have been described, it is initially intended that the configurations of the above-described embodiments and the examples may be appropriately combined or various modifications may be made.
[0340] The embodiments and examples disclosed herein are illustrative in all aspects and are not restrictive. The scope of the present invention is not limited to the embodiments and examples described above, but is indicated by the claims, and is intended to include all changes within the meaning and scope equivalent to the claims.
[0341] Explanation of symbols
[0342] 1 film forming apparatus, 2, 3 target material, 4 substrate holder, 5 substrate, 6 substrate heater, 7, 8 power supplies, 9 film forming bias power supply, 10 gas supply port, 11 exhaust port, 20 hard carbon film, 21 interface layer, 24 graphite phase, 25 amorphous phase, 30, 31 cutting tool, S1 spectrum of extracted pattern, S21 standardized spectrum, S4 spectrum from amorphous phase, A11, A12, A13, A21, A22, A23 peaks from graphite phase, L1 straight line, L2, L12, L22 vertical lines, a1, a3, b1, b3, c1, c3 approximate straight lines, a2, b2, c2 intersection points, P1 measured peak.
Claims
1. A cutting tool comprising: A substrate and a hard carbon film disposed on the substrate, The hard carbon film includes an amorphous phase and a graphite phase, The density of the hard carbon film is 2.5 g / cm 3 Above 3.5g / cm 3 the following, The hard carbon film has a crystallinity of 6.5% or less, the crystallinity of the hard carbon film being an index indicating a volume-based ratio of the graphite phase to the amorphous phase in the hard carbon film. The average coordination number of the amorphous phase is 2.5 or more and 4 or less, The surface of the hard carbon film has no liquid droplets.
2. The cutting tool according to claim 1, wherein: The thickness of the portion of the hard carbon film involved in cutting is not less than 0.1 μm and not more than 3 μm.
3. The cutting tool according to claim 1 or claim 2, wherein: The hard carbon film has a hydrogen content of 5 atomic % or less.
4. The cutting tool according to claim 1 or claim 2, wherein: The density of the hard carbon film is 3.0 g / cm 3 Above 3.5g / cm 3 the following.
5. The cutting tool according to claim 1 or claim 2, wherein: The density of the hard carbon film is 3.2 g / cm 3 Above 3.4g / cm 3 the following.
6. The cutting tool according to claim 1 or claim 2, wherein: The hard carbon film has a crystallinity of not less than 2% and not more than 6.5%.
7. The cutting tool according to claim 1 or claim 2, wherein: The hard carbon film has a crystallinity of 3% to 5%.
8. The cutting tool according to claim 1 or claim 2, wherein: The average coordination number of the amorphous phase is 3.5 or more and 4 or less.
9. The cutting tool according to claim 1 or claim 2, wherein: The thickness of the portion of the hard carbon film involved in cutting is 0.5 μm to 3 μm.
10. The cutting tool according to claim 1 or claim 2, wherein: The hard carbon film is composed of the amorphous phase and the graphite phase.
11. The cutting tool according to claim 1 or claim 2, wherein: The hydrogen content of the hard carbon film is not less than 0 atomic % and not more than 5 atomic %.
12. The cutting tool according to claim 1 or claim 2, comprising an interface layer disposed between the substrate and the hard carbon film, The interface layer comprises: At least one selected from the group consisting of: a single substance selected from the first group consisting of Group 4 elements, Group 5 elements, Group 6 elements, Group 13 elements, and Group 14 elements excluding carbon of the periodic table, an alloy or a first compound containing at least one element selected from the first group, and a solid solution derived from the first compound; or a second compound composed of at least one element selected from the first group and carbon, and one or both of a solid solution derived from the second compound, The thickness of the interface layer is greater than 0.5 nm and less than 10 nm.
13. The cutting tool according to claim 1 or claim 2, wherein: The substrate is made of WC-based hard alloy or metal ceramic.
14. The cutting tool according to claim 1 or claim 2, wherein: The substrate is composed of cubic boron nitride.
Citation Information
Patent Citations
Tool clad with amorphous carbon and its manufacturing method
JP2003062706A
Cutting tool
WO2016190443A1
DLC-coated tool
WO2008149824A1